Current Practice in the Treatment of Epithelial and Melanocytic Tumours with Interferon-α2b: A Survey of Tertiary Eye Centres in Germany - Jiang, Jana; Böhringer, Daniel; Auw-Hädrich, Claudia; Maier, Philip Christian; Barth, Teresa; Eter, Nicole; Fuest, Matthias; Geerling, Gerd; Heindl, Ludwig M.; Herwig-Carl, Martina; Hintschich, Christoph; Hufendiek, Katerina; Kampik, Daniel; Lieb, Wolfgang; Meller, Daniel; Mueller, Arthur; Pfeiffer, Norbert; Rehak, Matus; Schargus, Marc; Seitz, Berthold; Spitzer, Martin; Stahl, Andreas; Süsskind, Daniela; van Oterendorp, Christian; Wagner, Felix Mathias; Westekemper, Henrike; Ziemssen, Focke; Reinhard, Thomas (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose To evaluate the standard of care, in particular the use of topical or subconjunctival interferon-α2b, in treating ocular surface squamous neoplasia or melanocytic tumours in tertiary eye centres in Germany.Methods A survey containing 14 questions was sent to 43 tertiary eye centres in Germany. The questions addressed the surgical and medical management of ocular surface squamous neoplasia and melanocytic tumours (primary acquired melanosis and malignant melanoma), as well as the clinical experiences and difficulties in prescribing off-label interferon-α2b eye drops and subconjunctival injections.Results Twenty-four tertiary eye centres responded to the survey. Eighty-three percent of centres had used interferon-α2b in their clinical practice and 25% prescribed it as the first-line cytostatic agent following surgical excision of ocular surface squamous neoplasia, while 10% would do so for melanocytic tumours. Correspondingly, the majority of respondents selected mitomycin C as their first-line agent. Side effects were uncommon with topical interferon-α2b eye drops but were more frequently reported after subconjunctival interferon-α2b injections. In total, eight centres had experience with interferon-α2b injections. The most significant obstacles perceived by ophthalmologists when prescribing interferon-α2b were its high cost and the reimbursement thereof.Conclusion Off-label mitomycin C was the preferred adjuvant therapy for epithelial and melanocytic tumours, with interferon-α2b being the standard second-line option. Interferon-α2b has predominantly been used to treat ocular surface squamous neoplasia and, to a lesser extent, melanocytic tumours at German tertiary eye centres. Following its market withdrawal, supply shortages of interferon-α2b are likely to have a profound impact on patient care and their quality of life.
Keywords: 5-fluorouracil; mitomycin C; interferon-α2b; ocular surface squamous neoplasia; conjunctival melanoma